Child Drawing: A Projective Tool for Dental Anxiety Assessment - Ankita Yadav; Shalini Garg; Ankit Srivastava; Anil Gupta; Shikha Dogra; Sakshi Joshi (International Healthcare Research Journal, 2020)
INTRODUCTION: Assessment of child’s anxiety is important in order to determine the success of dental treatment. Drawing, a nonverbal, self-report, projective and non-invasive technique may prove be helpful and needs to be explored in order to access anxiety in children requiring dental treatment.AIM: To investigate the applicability of children’s drawings as an indicator to measure their level of anxiety.MATERIALS & METHOD: A cross-sectional study was conducted in a total of hundred children between age group of 4-6 years. Children were asked to draw dental operatory on A4 sheet and colour it with basic set of 12 colours. The drawing was scored using Child Drawing: Hospital (projective scale) scale and the results were compared with pulse oximeter readings (physiological parameter) and Venham Picture Test scorings.RESULTS: Child Drawing: Hospital scale scoring had a positive correlation with pulse oximeter reading (involuntary) (p-value = 0.125) and a negative correlation with Venham picture test (p-value = 0.140).CONCLUSION: Drawing may be statistically significant projective tool significant to assess child anxiety in dental setting.